Políticas sociais públicas como espaço para o resgate da cidadania: análise de um projeto de educação de adultos com famílias empobrecidas de cinco comunidades do município de Campos dos Goitacazes - Senna, Eunice de Hipólito (1993)
This work tries to analyse a guide project in the field of adult's education with rural workers that went through a process of proletarization, compelled to it by the violent and accelerated process of modernization of the agro-industry of sugar and alchool of the district of Campos dos Goytacazes. Had their sources of work been expropriated, 50% of this population were expelled from the rural are as in the period of 1950-91, considering that 25% of this amount were obliged to move to the city of Campos during the eighties, multiplying the slum's number from 13 to 30, in insalubrious and dangerous areas. Known data from the IBGE/IPEA display a present population of 26 thousand people, or 33% of the total amount of inhabitants of the district of Campos, that demands the urgent creation of housing programmes, of preventive health, education, leisure, professional skilling, jobs, etc. Given the brutality and intensity of the proletarization process of these rural workers, ever since the eighties, it is necessary that the municipal public power establishes as its priority action the implementation of specifical programs, and with adequate technology, to the assistance to these populations. The Project of Income' s Production through the street education's methodology, carried out by SPMDS during the years of 1990-92, shown up to be an adequate alternative to the deliverance of these population' s citizenship. Carried out at these people's environment and having as the main pedagogical purpose the recovering of their knowledge, this project had been constructed through the drawing of the main problems or questions brought about by these populations, what contributed to the rising or their participation leveIs, of self-esteem and self-confidence, as to the improving of the relationship between the agents of the project.